Neuropsychological evaluations associated with workplace accidents: a systematic review: Evaluaciones neuropsicológicas asociadas a accidentes laborales: una revisión sistemática - Vargas-María, Carlos-Antonio (Journal of Applied Cognitive Neuroscience, 2020)
Most occupational accidents are evidenced by a loss of worker control over the procedures they carry out. Objective: To establish the neuropsychological tests used to assess the cognitive profile of workers as a measure to prevent workplace accidents. Method: An advanced and manual systematic search of databases (PubMed / MedLine, Web of Science, Scopus, Science Direct, Cochrane Library) was performed to evaluate the neuropsychological tests used in work settings. Results: The systematic review yielded 1777 articles, of which 150 were pre-selected according to what was reported in the abstract and 57 validated for complete reading. 21 articles were used for the narrative synthesis with a sample of two thousand eight hundred and fifty-four (2,854) subjects; and a range of 18 to 60 years. Conclusion: The limited number of investigations that establish the neuropsychological profiles associated with occupational accidents are evident.